Validação do modelo mesoscópico de tráfego do SCOOT para o desenvolvimento de redes viárias urbanas microssimuladas - Aquino, Eduardo Araújo de (2012)
One of the main difficulties in the development of urban traffic microsimulation models is the collection of traffic data for calibration and validation. However, the city of Fortaleza has an important mesosimulation tool that, in addition to controlling urban traffic in real time, estimates traffic variables: the well-known SCOOT system. This system, implemented in cities around the world, controls and estimates traffic in the densest urban area of Fortaleza, based on the continuous detection of vehicle occupation on its more than 900 detectors spread throughout the city. However, because these data are simulated, they require validation before being used. The main aim of this work was to develop and implement a methodology to validate the mesoscopic simulation model of SCOOT, so its data can be used in the development of traffic microsimulation models, having as a case-study the system operating in Fortaleza. Based on experiments, the effects of two factors in the estimation error were investigated: the calibration of the parameter SATO, and the average travel time between the loop detector and the stop-bar. The results show that these two factors affect the quality of the prediction of volume, delay and number of vehicle-stops. These results contribute with a validation methodology that allows a better use of the data provided by SCOOT.